Towards the understanding of lubrication mechanisms in total knee replacements – Part II: Numerical modeling. (April 2021) - Marian, Max; Orgeldinger, Christian; Rothammer, Benedict; Nečas, David; Vrbka, Martin; Křupka, Ivan; Hartl, Martin; Wimmer, Markus A.; Tremmel, Stephan; Wartzack, Sandro
Abstract: Total knee replacements are an effective surgical treatment to restore the function of the knee. For an adequate design, knowledge about stresses and lubrication conditions is vital. Part II proposes a fully-coupled transient 3D model for the soft elastohydrodynamically lubricated contact based upon the generalized Reynolds equation and Finite Element Method while Part I of this study focused on experimental observations. Within the scope of this contribution, a numerical model is presented and validated with experimental data. Good agreement between model predictions and experimental data was found. A strong influence of fluid and geometry assumptions and transient effects were found. Besides, it was demonstrated that the rheological synovial fluid properties have a decisive role in the tribological behavior. Graphical abstract: Image 1 Highlights: Combination of experimental investigations with FEM-based numerical modeling. Good agreement when all relevant influencing factors are considered. Load and geometry dominated the pressure and film formation in the stance phase. The swing phase was largely influenced by the kinematics. The fluid film formation was largely affected by reversal points of motion.